El empleo informal en el departamento de Loreto y su relación con determinantes educativos y socioeconómicos durante el 2019 - Acosta Grandez, Wendy Patricia (2022)
Peru is a developing country, so it has experienced phenomena that usually occur in capitalist economic economies in developing countries, one of these problems is unemployment and informal employment. Although the country has experienced significant economic growth in recent decades, the impact of the formal sector on the workforce has not increased, which is why a large number of people are forced to carry out work activities outside the scope of the labor force. inspection in which it is not applied or does not comply with the law and current labor regulations and does not promote their compliance; In other words, these informal workers are outside the law and regulatory framework that governs economic activities, they do not have health insurance, pension insurance and receive non-salary income. The results found in the present study allow us to confirm the proposed hypothesis, in relation to the educational and socioeconomic factors that are related to the informality of the labor market in the Loreto region, and that influence the probability that individuals belong to the informal sector; These factors are income, hours of work, years of education, age, and race or ethnicity with which individuals identify. Our work shows another approach to cover the problem of informality, since it indicates that informality is the cause of other social problems such as inequality and lack of access to education, low salary perceptions on the part of the less qualified population and possibly discrimination implicit given by access to education to individuals who identify with minority races or ethnicities. Therefore, to reduce informality it is also necessary to address these social, educational and cultural problems.